Impacts of Nurse Turnover in Hospitals: A Systematic Review of Economic and Non-Economic Factors - Dr. Syed Sheheryar Ali Kazmi; Dr. Hafiz Adnan Majeed; Sahibzada Waqar Ahmad (Journal of Business Insight and Innovation, 2026)
Purpose: This study examines and synthesizes the non-economic and economic impacts of nurse turnover in acute hospitals, addressing a critical concern for the healthcare industry. Design/Methodology/Approach. Utilizing the Preferred Reporting Items for Systematic Reviews and Meta-Analyses checklist, researchers reviewed 16 articles from 9,041 initially identified, focusing on non-experimental quantitative studies, original research, and English language publications. Findings. Findings reveal that nurse turnover is costly, negatively impacts workgroup processes, nurse staffing, and patient outcomes, with seven studies investigating associations between turnover and outcomes, while nine confirm its economic burden. The study concludes that most research emphasizes the adverse non-economic and economic consequences of turnover, underscoring the need for healthcare organizations, nurse managers, and policymakers to develop retention strategies and implementation frameworks to mitigate these effects and enhance hospital competency in improving care quality and patient safety. Research Limitations. The review acknowledges several constraints, including possible publication bias, database selection limitations, and exclusive focus on acute care settings which precludes generalization to long-term care or community healthcare environments. Practical Implications. The findings provide healthcare administrators and policymakers with empirical evidence to design evidence-based retention strategies that reduce financial burdens, improve patient care quality, and enhance workforce stability. Originality/Value. This study contributes to the literature by providing a comprehensive synthesis of both economic and non-economic impacts of nurse turnover in acute hospitals, addressing a gap where previous reviews predominantly focused on turnover determinants rather than consequences. References References Alhomoud, F. (2025). ‘That’s Enough’-Workplace Violence Against Physicians, Pharmacists, and Nurses in Saudi Arabia: A Systematic Review of Prevalence, Causes, and Consequences. In Risk Management and Healthcare Policy (Vol. 18). https://doi.org/10.2147/RMHP.S509895 Awalkhan, A. (2018). Nursing Education in Pakistan, Trends and Challenges of Future. Higher Education Research, 3(1). https://doi.org/10.11648/j.her.20180301.12 Bae, S. H., Mark, B., & Fried, B. (2010). Impact of nursing unit turnover on patient outcomes in hospitals. Journal of Nursing Scholarship, 42(1). https://doi.org/10.1111/j.1547-5069.2009.01319.x Cooray, A., & Wickremasinghe, G. (2007). The Efficiency of Emerging Stock Markets: Empirical Evidence from the South Asian Region. The Journal of Developing Areas, 41(1). https://doi.org/10.1353/jda.2008.0030 Evans, J. M., Brown, A., & Baker, G. R. (2015). Intellectual capital in the healthcare sector: A systematic review and critique of the literature. In BMC Health Services Research (Vol. 15, Number 1). BioMed Central Ltd. https://doi.org/10.1186/s12913-015-1234-0 Halter, M., Boiko, O., Pelone, F., Beighton, C., Harris, R., Gale, J., Gourlay, S., & Drennan, V. (2017). The determinants and consequences of adult nursing staff turnover: A systematic review of systematic reviews. In BMC Health Services Research (Vol. 17, Number 1). BioMed Central Ltd. https://doi.org/10.1186/s12913-017-2707-0 Hassan, S. (2023). Nursing Shortage in Pakistan. NURSEARCHER (Journal of Nursing & Midwifery Sciences). https://doi.org/10.54393/nrs.v3i01.39 Iqbal, H. H., Siddique, A., Qadir, A., Ahmad, S. R., Liess, M., & Shahid, N. (2024). Human health and ecology at risk: a case study of metal pollution in Lahore, Pakistan. Environmental Sciences Europe, 36(1). https://doi.org/10.1186/s12302-023-00824-2 Lee, G. R., Lee, I., Chung, M., & Ha, J. (2024). Effects of grit, calling, and resilience on the retention intention of general hospital nurses. International Nursing Review, 71(4). https://doi.org/10.1111/inr.12908 Li, C., Cui, X., Zhao, Y., Xin, Y., Pan, W., & Zhu, Y. (2024). Missed Nursing Care as a Mediator in the Relationship between Career Calling and Turnover Intention. International Nursing Review, 71(1). https://doi.org/10.1111/inr.12842 Majeed, I. (2025). Confronting the Challenges of Nursing in Pakistan. NURSEARCHER (Journal of Nursing & Midwifery Sciences). https://doi.org/10.54393/nrs.v5i2.176 Malik, O. F., Sattar, A., Shahzad, A., & Faiz, R. (2020). Personal Bullying and Nurses’ Turnover Intentions in Pakistan: A Mixed Methods Study. Journal of Interpersonal Violence, 35(23–24). https://doi.org/10.1177/0886260517719903 Morais, M. G. de, Silva, I. M. A. de O. e, Versiani, E. R., Silva, C. C. G. da, & Moura, A. S. de. (2021). Mental health support services for medical students: a systematic review. Revista Brasileira de Educação Médica, 45(2). https://doi.org/10.1590/1981-5271v45.2-20200428.ing Munir, F., Mehmood, K. A., & Nawaz, S. (2022). Fiscal Decentralization and Health Outcome: Case of Pakistan. Journal of Social Sciences Review, 2(3). https://doi.org/10.54183/jssr.v2i3.71 Ren, H., Li, P., Xue, Y., Xin, W., Yin, X., & Li, H. (2024). Global Prevalence of Nurse Turnover Rates: A Meta-Analysis of 21 Studies from 14 Countries. In Journal of Nursing Management (Vol. 2024). John Wiley and Sons Ltd. https://doi.org/10.1155/2024/5063998 Salvage, J., & White, J. (2019). Nursing leadership and health policy: everybody’s business. In International Nursing Review (Vol. 66, Number 2). https://doi.org/10.1111/inr.12523 Sumaira Khowaja Punjwani. (2020). Nursing in Pakistan: issues and challenges. Eubios Journal of Asian and International Bioethics, 30(5). Yasir, M., Majid, A., Javed, A., Khan, Z. A., Malik, S., Naz, F., & Ul Islam, E. (2020). INQUIRING VOLUNTARY TURNOVER FOR FEMALE NURSES IN PAKISTAN THROUGH FOCUSED ETHNOGRAPHY. Journal of Ayub Medical College, 32(2).